Bird Diversity in Open Green Spaces in Pangkalpinang City - Nur Annis; Aeng Saputra (Biology Study Program, Faculty of Science and Engineering, University of Bangka Belitung, Indonesia, 2025)
Urban development and construction can have both positive and negative impacts. Negative impacts include traffic jams, flooding, drought, water and air pollution, and various other environmental problems. Increasing green open spaces (or Ruang Terbuka Hijau, hereafter RTH) is expected to provide solutions to minimize the negative impacts of development. The presence of vegetation in RTH is expected to act as a water catchment area, neutralize pollutants, and act as the city's lungs as it serve as habitat for various animals, including birds. This study aims to explore bird diversity in RTH in Pangkalpinang City. Data collection was conducted in May 2019 in four city parks in Pangkalpinang City: Lapangan Merdeka Square, Wilhelmina Park, Timah Complex Park, and Bhayangkari Babel Park. A total of 227 individuals from 16 bird species from three orders and eight families were found at the study sites. In general, bird diversity in the four locations is considered as low to moderate. There is a tendency for an increase in bird diversity along with the increasing amount of vegetation in each RTH. Passeriformes (a group of songbirds) are the most commonly found group. This supports the function of green open space in Pangkalpinang City in providing recreational services for urban residents, in addition to other ecological services that birds can provide to support the green space's function. Among RTH we visited, Taman Komplek Timah is the most bird-friendly green space.